DEFINITION PUBLIC ADMINISTRATION PRINCIPLES IN REGULATORY DOCUMENTS OF UKRAINE - Baranov , A. (Pressing Problems of Public Administration, 2019)
The article analyzes international documents, strategic documents, laws of Ukraine that shape the principles of public administration in Ukraine, and identifies the place and role of these principles in shaping public administration in Ukraine. It is noted that the principles of public administration, which are based on administrative law, are common to Western European countries, namely the principles of reliability and predictability; openness and transparency; accountability; efficiency and effectiveness were reflected in the framework of public administration reform, in particular in the law of Ukraine “On Civil Service” in the principles of public service. Unlike the law of Ukraine on “On Local Self-Government in Ukraine” and “On Service in Local Self-Government Bodies”, where the above principles are practically not taken into account or partially taken into account. At the same time, they exist in a different context. The analysis shows that Ukraine’s strategic documents do not necessarily outline the generally accepted democratic principles in their content, but they are also reflected in the texts of the documents themselves, as well as the laws of Ukraine, which they adopt after signing the Association Agreement between Ukraine, on the one hand, and The European Union, the European Atomic Energy Community and their Member States, on the other hand, and are committed to fulfilling their commitments. Implementation of the main principles laid down in the Charter of the United Nations, the Organization for Security and Co-operation in Europe (OSCE), in particular the Helsinki Final Act of the Conference on Security and Co-operation in Europe 1975, the concluding documents of the Madrid and Vienna Conferences of 1991 and 1992 respectively, the Paris Charter for a New Europe of 1990, the UN Universal Declaration of Human Rights of 1948 and the Council of Europe Convention on Human Rights and Fundamental Freedoms of 1950, set out in the Association Agreements between Ukraine, of the one part, and the European Union, the European Atomic Energy Community, and their Member States, of the other part in Ukraine’s strategic documents, laws, and other regulations are a prerequisite and prospect of EU membership.